1999
DOI: 10.3354/meps191127
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic characterisation of micronekton distribution in French Polynesia

Abstract: Tuna distribution may be directly linked to food ava~labllity, the density of which can be assessed by echo-sounding. A study was performed in the French Polynesian EEZ (Economic Exclusive Zone) between 1995 and 1997 with a 38 kHz echo sounder working down to 500 m depth. With the settings used, acoustic back-scattered energy may be considered as representative of micronektonic fish biomass and provided information on horizontal and vertical micronekton variabilities and the structure of the echograms. Three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…Even if any doubt remains about the influence of fish-luring light, the dominant stomach contents of the recaptured fish were lantern fish and squid (Table 1). These species are reported to form a sound scattering layer (SSL) and showed the same diurnal vertical migration as tuna (Bertrand et al 1999). Josse et al (1998) indicated the important role of the SSL, assimilated as food, in vertical and horizontal tuna movements, during daytime and night time.…”
Section: Discussionmentioning
confidence: 99%
“…Even if any doubt remains about the influence of fish-luring light, the dominant stomach contents of the recaptured fish were lantern fish and squid (Table 1). These species are reported to form a sound scattering layer (SSL) and showed the same diurnal vertical migration as tuna (Bertrand et al 1999). Josse et al (1998) indicated the important role of the SSL, assimilated as food, in vertical and horizontal tuna movements, during daytime and night time.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern was stronger when surface phytoplankton biomass was higher, which was the case during OUTPACE due to the high contribution of diazotrophs at this season. In the W-MA and CE-MA regions, copepods dominated the mesozooplankton taxonomic structure, but the sampling of teleost eggs and juveniles of euphausiaceae, although certainly under-sampled with our bongo net, do indicate the presence of higher trophic levels in deeper waters in this region (Roger et al 1994;Bertrand et al, 1999). 20…”
Section: Estimation Of the Trophic Interactions Between Mesozooplanktmentioning
confidence: 99%
“…The integration threshold was set at -80dB. At 38 kHz, s A is representative of the micronekton abundance (Bertrand et al 1999). Echograms graphically represent the acoustic back-scattered energy; micronekton aggregations can be tracked on echograms.…”
Section: Introductionmentioning
confidence: 99%